Improvement of oral health-related quality-of-life by use of different kinds of double-crown-retained removable partial dentures - Stober, Thomas; Danner, Daniel; Bömicke, Wolfgang; Hassel, Alexander J. (Acta odontologica Scandinavica, 2016)
Objective. To verify the hypotheses that treatment with double-crown-retained removable partial dentures (RPDs) improves oral health-related quality-of life (OHRQoL) over a 36-month period and that the performance of RPDs retained by use of electroplated double crowns (EP-RPDs) was different to that of RPDs retained by use of cast double crowns (C-RPDs). Materials and methods. Fifty-four patients (mean age = 64 years, 63% men) were recruited and randomly assigned to C-RPD or EP-RPD. OHRQoL was assessed pre-treatment, post-treatment and 6, 12, 24 and 36 months after insertion, by use of the oral health impact profile (OHIP). An unweighted total score was calculated (OHIP-SUM). A two-level hierarchical model was used for statistical analysis. First-level units were the measurements on the six occasions; second-level units were the patients. Results. Improvement of OHRQoL was observed in both groups after treatment (t = 7.27, p < 0.001). Whereas a treatment-material interaction indicated that treatment with EP-RPDs resulted in greater immediate improvement of OHRQoL, a time-material interaction indicated that long-term improvement was greater for C-RPDs. Conclusions. Treatment with EP-RPDs and C-RPDs improved OHRQoL initially. Over a period of 36 months the effect was significant. The treatment is, therefore, a promising therapeutic option. The cast conical design seems to have advantages with regard to long-term OHRQoL.